2017
DOI: 10.1017/s1751731116001956
|View full text |Cite
|
Sign up to set email alerts
|

Combination of legume-based herbage and total mixed ration (TMR) maintains intake and nutrient utilization of TMR and improves nitrogen utilization of herbage in heifers

Abstract: Diets combining herbage and total mixed rations (TMR) are increasingly used in temperate regions for feeding ruminants, but little information is available regarding the effects on nutrient intake and digestion of this feeding management in beef cattle. The aim of this study was to determine the effects of combining TMR (10% CP and 13% ADF), and legume-based herbage (14% CP and 27% ADF) on intake, nutrient digestion, ruminal fermentation, microbial N flow and glucose and nitrogen metabolism in heifers. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…In contrast, Bargo et al [ 42 ], observed a positive association between serum urea levels and pasture protein content. Despite higher CP concentrations of pasture, Santana et al [ 43 ] and Kohn [ 44 ] reviewed that milk or blood urea N are indicators for diet adequacy and nitrogen utilization efficiency in lactating dairy cattle. This underlines the energy deficit of the PG and rumen microflora of PG cows, resulting in ammonia excessively passing into the bloodstream and being converted to urea in the liver, or leading to an increased endogenous amino acids catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Bargo et al [ 42 ], observed a positive association between serum urea levels and pasture protein content. Despite higher CP concentrations of pasture, Santana et al [ 43 ] and Kohn [ 44 ] reviewed that milk or blood urea N are indicators for diet adequacy and nitrogen utilization efficiency in lactating dairy cattle. This underlines the energy deficit of the PG and rumen microflora of PG cows, resulting in ammonia excessively passing into the bloodstream and being converted to urea in the liver, or leading to an increased endogenous amino acids catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Pasture supplementation with TMR (mixture of forage and concentrates) appears as a strategy that can improve the uptake of N-ammonia and improve microbial protein synthesis on a forage-based diet in cattle [116]; but in sheep, this approach has been little explored. Our group evaluated different levels of fresh forage supplementation to a total mixed ration (TMR) (0, 0.50, 0.75, and only fresh forage) in lambs.…”
Section: Digestion Of Temperate Forages Plus Other Feedstuffsmentioning
confidence: 99%
“…Most of the work done with temperate pastures as the only food, and with the aggregate of concentrates or ration completely mixed, have been carried out in dairy cattle [116,[119][120][121]. If these effects could be demonstrated in sheep, this strategy could be used to produce high yields of high-quality lamb meat with the inclusion of high levels of fresh forage.…”
Section: Combining Pastures With Tmr Diets For Finishing Lambsmentioning
confidence: 99%
“…where, P is the average power, kW; P 1 is the initial power, kW; P 2 is the working power, kW; P 3 is the final power, kW. Y = 77.34 + 2.45A + 2.07B + 3.92C + 2.30D + 4.53E + 1.64AB -1.92AC -2.36AD -2.38AE -3.13BC -0.83BD -1.98BE + 0.49CD -1.23CE -2.60DE -2.78A 2 -2.37B 2 -5.16C 2 -1.28D 2 -3.04E 2 (7) P = 7.57 + 1.60A + 0.24B + 0.50C + 0.78D + 0.14E + 0.27AB -0.17AC -0.066AD -0.13AE -0.35BC + 0.17BD + 0.13BE + 0.33CD -0.022CE + 0.053DE + 0.19A 2 -0.089B 2 -0.019C 2 -0.089D 2 + 0.087E 2 (8)…”
Section: Evaluation Indexmentioning
confidence: 99%
“…Large-scale breeding is an important meat sheep breeding method because of its advantages of high rate of domestic animals for sale, remarkable economic benefits and easy to manage [1][2][3] . Total mixed rations (TMR) denotes the balanced diet that can be obtained based on the nutritional requirements of ruminants at different stages of growth and development to ensure a balanced feed intake for ruminants, improve the utilisation rate of crude feed, facilitate production of sheep breeding, environmental control and satisfy the requirements of modern meat sheep standardisation and intensification.…”
Section: Introduction mentioning
confidence: 99%